2008
DOI: 10.1097/pec.0b013e31818ea04c
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Waiting Room Stress

Abstract: Music is an easy and useful way to decrease the anxiety of visitors in an emergency department waiting area. Although no difference was detected for the aromatherapy group, this could be because of environmental conditions or imprecise application of the aromatherapy; further study is needed to either prove or disprove its effectiveness in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 8 publications
1
19
1
Order By: Relevance
“…Besides, the air-conditioning system of the hospital could have decreased the strength of the aroma. Apparently, aromatherapy could not be successful under such conditions (2). Finally, as we did not detect any significant differences between the two groups in terms of the mean first- and fifth-minute Apgar scores, aromatherapy with C. aurantium did not seem to have any adverse effects on the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the air-conditioning system of the hospital could have decreased the strength of the aroma. Apparently, aromatherapy could not be successful under such conditions (2). Finally, as we did not detect any significant differences between the two groups in terms of the mean first- and fifth-minute Apgar scores, aromatherapy with C. aurantium did not seem to have any adverse effects on the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 80% of women in labor have anxiety disorders (2). According to the control theory, there is a relationship between pain and psychological problems like anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…[22232841] Toet et al . reported that additional distraction sources in the waiting rooms of large dental clinics, such as great background activity and continuous going and coming of patients, might influence the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the aromatherapy potency could be explained by environmental conditions or the inexact application of the EO. So the author suggested future studies to either confirm or not confirm its effectiveness in this setting …”
Section: Anxiolytic Actionmentioning
confidence: 99%